2012
DOI: 10.3163/1536-5050.100.4.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine at the intersection of research interests between academic health sciences librarians and medical educators: a review of the literature

Abstract: Scholarship of EBM instruction is of common interest between medical educators and health sciences librarians. Coauthorship between the groups and distribution of literature points to a productive collaboration. An emerging literature of controlled studies measuring the impact of cross-disciplinary efforts signals continued progress in the arena of EBM instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Several authors have published articles focusing on the teaching of EBM skills to medical students with the participation and collaboration of a librarian greater responsibilities in students' development of EBP skills. Dorsch and Perry (2012) conducted a literature review on the intersection of EBP and information literacy in both library and medical professional literature; they concluded that this topic is of similar interest for the two professional groups. While there are many studies involving EBP, librarians, and other medical professionals or teaching faculty, the authors were unable to find any studies that measured students' self-confidence in performing the discrete information literacy skills that affect sound EBP skills.…”
Section: Evidence Based Practice and Its Connection To Information LImentioning
confidence: 99%
“…Several authors have published articles focusing on the teaching of EBM skills to medical students with the participation and collaboration of a librarian greater responsibilities in students' development of EBP skills. Dorsch and Perry (2012) conducted a literature review on the intersection of EBP and information literacy in both library and medical professional literature; they concluded that this topic is of similar interest for the two professional groups. While there are many studies involving EBP, librarians, and other medical professionals or teaching faculty, the authors were unable to find any studies that measured students' self-confidence in performing the discrete information literacy skills that affect sound EBP skills.…”
Section: Evidence Based Practice and Its Connection To Information LImentioning
confidence: 99%
“…Studies have shown that teaching EBP skills to health professional students results in an increase in knowledge and skills [48][49][50]. Library instructors often utilized a combination of teaching formats, usually lecture combined with lab practice and/or small group discussion (18 out of 27 studies), suggesting that the instructors felt that the use of a combination of teaching methods was the best approach.…”
Section: Methods Of Instructionmentioning
confidence: 99%
“…Depending on the circumstances and opportunities, librarians can do well in any role and contribute at all levels in the EBP teaching process [49]. Teaching information skills seems to be the most common role for librarians in EBP instruction, and research has indicated that librarians may have better learning outcomes for one-shot, face-to-face information literacy sessions than nonlibrary instructors [51].…”
Section: Role Of Librarians In Ebpmentioning
confidence: 99%